Leading higher education transformation: The role of student affairs (Journal of Student Affairs in Africa, 2023)
Student affairs practitioners and researchers are well positioned to contribute holistically tostudent success and as such could play a strategic role in the transformation of higher education.The aim of this article is to illustrate that a key strategic objective of student affairs is to contributesignificantly towards student success. This article reports on a study (January, 2021) entitled ‘Towardsa qualitative framework for blending equity and excellence in transforming South African highereducation transformation to achieve development’ in which the promotion of student success isviewed as central to institutional transformation. The purpose of the study was to contribute to amore comprehensive qualitative framework for higher education transformation in South Africa byreconciling notions of ‘equity and excellence’. Interviews were conducted with sixteen leaders in thefield of higher education in South Africa. Thereafter, interview data were triangulated with strategicdocuments of various entities concerned with higher education transformation. The theoreticalframework encapsulated the human capital and human capability theories and argues further fora reconciliation of these theories to promote social justice and human well-being. The study usedgrounded theory methods to analyse and present the comprehensive qualitative framework. Thestudy found that student success was the most critical factor driving institutional transformation. Inaddition, four other interrelated elements were presented as the core elements of a comprehensiveframework. Based on these findings, this article explores the implications for student affairs further,using unpublished input gathered by the author through reflective conversations with stakeholdersat the University of Cape Town. In this regard the notion of a set of student learning imperatives(graduate attributes) becomes relevant to the discussion when student affairs practitioners andresearchers collaborate with faculties and departments on strategic projects.